IMPROVING STUDENTS SPEAKING SKILL THROUGH ZOOM APPLICATION FOR COLLEGE STUDENTS - Dadan Hidayat (INOVISH JOURNAL, 2022)
Abstract :This study aimed to see how the Zoom Application can affect students' speaking skills during online learning during the pandemic covid-19. The experimental research method was used in this study. This action research started with an observation in which the researcher The subject was a group of 30 third-semester students from the University Bina Sarana Informatika in the academic year 2020-2021. This study used some instruments as observation to collect data, which provides complete concern to the research object of the sense, which aims to explain the situation in-class activities, individual involvement in some activities, and the relationship between situation, activity, and individual. Documentation is used to obtain explicit information and to administer a test in the form of a multiple-choice question. Data was collected and analyzed in qualitative and quantitative ways to explain the results of observations and tests. In the result,  the researcher find out the average score of the students‟ speaking test was 59.1 from 30 students. Later on, the average score for speaking in Post-Test I was 79.2, and Post-Test II was 85.7. t could be concluded that using a zoom application can affect speaking ability significantly[u1]  [u1]Abstact has been revised based on the request. Thank you